Molecular docking study of natural alkaloids as multi-targeted hedgehog pathway inhibitors in cancer stem cell therapy. (June 2016) - Mayank,; Jaitak, Vikas
Abstract: Cancer is responsible for millions of deaths throughout the world every year. Increased understanding as well as advancements in the therapeutic aspect seems suboptimal to restrict the huge deaths associated with cancer. The major cause responsible for this is high resistance as well as relapse rate associated with cancers. Several evidences indicated that cancer stem cells (CSC) are mainly responsible for the resistance and relapses associated with cancer. Furthermore, agents targeting a single protein seem to have higher chances of resistance than multitargeting drugs. According to the concept of network model, partial inhibition of multiple targets is more productive than single hit agents. Thus, by fusing both the premises that CSC and single hit anticancer drugs, both are responsible for cancer related resistances and screened alkaloids for the search of leads having CSC targeting ability as well as the capability to modulating multiple target proteins. The in silico experimental data indicated that emetine and cortistatin have the ability to modulate hedgehog (Hh) pathway by binding to sonic hedgehog (Hh), smoothened (Smo) and Gli protein, involved in maintenance CSCs. Furthermore, solamargine, solasonine and tylophorine are also seems to be good lead molecules targeting towards CSCs by modulating Hh pathway. Except solamargine and solasonine, other best lead molecules also showed acceptable in silico ADME profile. The predicted lead molecules can be suitably modified to get multitargeting CSC targeting agent to get rid of associate resistances.